Comparison of clinical and virological features in pediatric and adult dengue cases at Insein General Hospital during Myanmar’s 2022 dengue season - Htin Lin; Mya Myat Ngwe Tun; Yin Mon Wint Zin; Khin Theingi Myint; Win Kay Khine; Khine Mya Nwe; Aye Aye Thant; Thin Thin Shwe; Win Mar; Khin Sandar Aye; Khaing Moe Aung; Yuki Takamatsu; et al. (Tropical Medicine and Health)
Abstract Background Myanmar is one of the countries in Southeast Asia where serious dengue outbreaks occur and Yangon is among the regions with the highest number of cases in the country. Many infections including dengue are common in Yangon during the rainy season, and co-infections may also occur. Adults are more likely than children to experience co-infections of dengue and other diseases. Although pediatric dengue has been studied in Yangon for decades, research on adult dengue is scant. Therefore, this study compared the clinical and virological characteristics of pediatric and adult dengue cases in Yangon. Methods This cross-sectional study was conducted at Insein General Hospital in Yangon, Myanmar, from June to September 2022. We recruited 221 suspected dengue patients (134 children and 87 adults), with or without other diseases, and tested their dengue serological markers using a serological method and their dengue virus (DENV) serotypes using conventional RT-PCR. Chi-squared and Fisher’s exact tests were conducted to assess significance. Results The dengue non-structural protein-1 antigen (NS1Ag) positivity was 37% in children and 32% in adults. DENV serotypes were identified in 80% of NS1Ag-positive patients. Among NS1Ag-positive cases, the DENV-1 serotype predominated (67%), followed by DENV-2 (17%), DENV-3 (9%), DENV-4 (5%), and mixed DENV-1 and DENV-2 (2%) serotypes. Shock was observed in 14% of children and 3% of adults. Anti-dengue IgG antibody positivity was positively correlated with dengue shock. Three pediatric dengue cases (6%) also had other infections including bronchiolitis, ear infection, and diarrhea. Seven adult dengue cases (25%) also had other diseases including advanced HIV infection, severe pneumonia, tonsillitis, thyroid disease, cholecystitis, drug poisoning, and thalassemia. Conclusion The serotype distribution and clinical presentations of pediatric and adult dengue cases were not significantly different, but adults were more likely to have dengue together with other diseases than children. This study provides information for the better management of febrile children and adults in hospital settings and provides a foundation for nationwide epidemiological studies on dengue serotypes and modifications of the national guidelines for dengue management in Myanmar.